2012
DOI: 10.1080/01411926.2010.550271
|View full text |Cite
|
Sign up to set email alerts
|

Learning citizenship through social participation outside and inside school: An international, multilevel study of young people's learning of citizenship

Abstract: In this article we revisit and re-analyse data from the 1999 IEA CIVED transnational study to examine the factors associated with the ways in which young people learn positive attitudes towards participation in, and knowledge and skills about democracy. Less formal learning, wherever it takes place, has recently been conceptualised as a process of social participation, and we explore its effects using Lave and Wenger's and Wenger's understanding of learning through communities of practice. This is then contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 27 publications
1
49
0
7
Order By: Relevance
“…Hoskins et al, 2012;Sohl & Arensmeier, 2015), we should strengthen further the bottom-up perspective on politics, focusing on the (extended) public sphere as a central arena for participation. This focus includes empowering students through participation in discussions, practice in facing opposition and critically reviewing arguments and political information in social media (Journell et al, 2015), including rhetoric with emotional appeal.…”
Section: Discussionmentioning
confidence: 99%
“…Hoskins et al, 2012;Sohl & Arensmeier, 2015), we should strengthen further the bottom-up perspective on politics, focusing on the (extended) public sphere as a central arena for participation. This focus includes empowering students through participation in discussions, practice in facing opposition and critically reviewing arguments and political information in social media (Journell et al, 2015), including rhetoric with emotional appeal.…”
Section: Discussionmentioning
confidence: 99%
“…Higher cognitive ability is also positively related to democratic participation indicated by, for example, voter participation and support for free speech (Dee 2004;Hauser 2000). In citizenship studies, cognitive ability is typically measured by a general measure of intelligence, a measure that combines verbal and mathematics abilities, or using (expected) educational level as a proxy (Geijsel et al 2012;Hoskins, Janmaat, and Villalba 2012;Isac et al 2011;Lopez et al 2009;Quintelier 2010;Schulz et al 2010). However, educational level has been shown to have an effect on civic engagement independent of cognitive ability (Hauser 2000), while general measures of cognitive ability or measures that combine different types of cognitive ability may veil which component of cognition positively relates to citizenship development.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to those from Dassonneville et al (2012), who found no association between average classroom climate and students' political self-efficacy. Furthermore, the magnitude of school or classroom differences was low even in the studies that revealed statistically significant effects of average open classroom on students' political self-efficacy (Hoskins et al, 2012;Manganelli et al, 2015). Hence, contextual characteristics such as open classroom or positive student relationships seem to have only a limited general association with students' political self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the definitions of an open classroom differs slightly across studies, the usual core elements include the possibility to engage in respectful debates and to express opinions on public issues. Previous studies have shown the positive relation of open classroom climate not only to students' political self-efficacy (Godfrey & Grayman, 2014;Manganelli et al, 2015;Perliger, Canetti-Nisim, & Pedahzur, 2006) and confidence in school participation (Godfrey & Grayman, 2014;Torney-Purta, Barber, & Richardson, 2004), but also to other related constructs, such as political trust (Claes, Hooghe, & Marien, 2012;Dassonneville, Quintelier, Hooghe, & Claes, 2012), political knowledge (Campbell, 2008;Hoskins, Janmaat, & Villalba, 2012), or pro-participatory attitudes and actual political participation (Campbell, 2008;Hooghe & Dassonneville, 2013;Hoskins et al, 2012;Manganelli et al, 2015;Perliger et al, 2006;Quintelier & Hooghe, 2013).…”
Section: Development Of Political Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation